Characteristics of cell morphology in different stages of Schizochytrium mangrovei PQ6’s life cycle - Hong, Dang Diem; Nhat, Pham Van; Lan Anh, Hoang Thi (Academia Journal of Biology, 2016)
Schizochytrium mangrovei PQ6 is a heterotrophic marine microalga, which was isolated from Phu Quoc Island, Kien Giang province in 2006-2008. This is a potential strain for multiuse, such as live food for some aquaculture animals, raw material for functional food production, bio-oil rich in polyunsaturated fatty acids omega-3 and omega-6 (PUFAs omega-3/6), feedstock for biodiesel production, squalene for pharmacy application. However, basic research on the life cycle of this species has not yet been announced in all over the world as well as in Vietnam. The life cycle of this species is very complex including many stages with diferent cell types. In this article, we present the results of characteristics of cell morphology which were observered in different stages of PQ6 strain’s life cycle, such as cell types, type and time of cell division as the basis for classifying species, determine the development stages of cells in order to provide the scientific basis for the proceeding to determine ploidy and the genome size. In the life cycle of alga S.mangrovei PQ6, the development was in three ways as: production of zoospores, amoeboid and cell dividing by style of vegetative cells division. The time that have required for the cycle of cell division under the above styles mentioned was about from 8.5 hours to 10.8 hours, depending on the size and cell status which were selected for the initial observations under our experimental conditions. In addition, the scientific evidences on changes in cell morphology in the life cycle of this alga has provided new additional scientific data for this microalgal species which had identified scientific name of Schizochytrium mangrovei PQ6 based on the morpholigical characteristics and sequence of 18S rRNA gene reported previousely.